INOVASI PUSTAKAWAN DI MASA GEMPURAN PANDEMI COVID-19 - Merdansah Merdansah (UIN Imam Bonjol Padang, 2020)
With the current Covid 19 pandemic conditions, librarians must become literacy ambassadors (Literacy Ambassadors) for even though users in any circumstances and conditions. To become literacy ambassadors (Literacy Ambassadors), various innovations that can be done are the discovery of several new ideas, practices, or artifacts for the adoption unit. For that, some of the skills a librarian must have, namely (1). education and skills about librarianship (2). skills in the use of information technology (3). Leadership (4). language skills (5). knowledge of the needs of users, and (6) Creativity - with the available resources (Creativity-with the available resources